Late onset GM2-gangliosidosis: Clinical, pathological, and biochemical studies on 8 patients. Issue 10 (October 1973) - Brett, E. M.; Ellis, R. B.; Haas, L.; Ikonne, J. U.; Lake, B. D.; Patrick, A. D.; Stephens, Rosemary
Abstract : Eight cases of late onset GM2 -gangliosidosis are described. 4 presented before the age of 2 years and 4 between 3½ and 10 years. Gait disturbance, intellectual deterioration, and fits were prominent features. Optic atrophy was seen at a late stage in 2 patients. An exaggerated startle reaction to sound and an unusual type of cherry red spot at the macula were seen for the first time in this condition. Pathological changes were similar to those described in Tay-Sachs disease. There was an increase in the amount of a ganglioside chromatographically identical with that found in Tay-Sachs disease. A partial deficiency of hexosaminidase A was found in 2 cases and a profound deficiency in 4. There was no correlation between the age of onset of symptoms and the degree of enzyme deficiency. The evidence presented is consistent with an autosomal recessive mode of inheritance.